Frontiers of the Roman Empire = Frontières de l'Empire Romain. - Breeze, David J. (Archaeopress Archaeology, 2021)
The Roman military remains of Egypt are remarkable in their variety and state of preservation: forts, quarries whose materials were used in the monumental buildings of Rome, roads which brought the Mediterranean into contact with the Indian Ocean; each reader of this book will enjoy learning more about the remarkable Roman inheritance of Egypt.